A genome?wide analysis of NPF and NRT2 transporter gene families in bread wheat provides new insights into the distribution, function, regulation and evolution of nitrate transporters. - Li, M.; Tian, H.; Gao, Y.
Nitrate transporters (NRT)in plants are mainly encoded by the NPF and NRT2 gene families. We aimed to reveal the chromosome distribution, collinearity, coexpression and evolution of the NPF and NRT2 genes in the genome of wheat (Triticum aestivum). Nitrate transport activity of representative proteins was also verified.
Keywords: NPF; NRT2; WHEAT; EXPRESSION; FUNCTION; EVOLUTION